Komunikasi Interpersonal Divisi Front Office Dalam Menangani Komplain Pasien di Natasha Klinik Center - Bariah, Ira Hoeril (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examined the role of interpersonal communication of the front office division in handling patient complaints at Natasha Clinic Center. Interpersonal communication holds a central role in creating quality healthcare services and building positive relationships between healthcare personnel and patients. The front office division serves as the frontline guard in direct interaction with patients, both when welcoming, providing information, and handling complaints or complaints. This qualitative descriptive research aimed to describe and analyze the forms of interpersonal communication engaged in by front office staff, their supporting and hindering factors, as well as the impact of interpersonal communication on patient satisfaction after submitting a complaint at Natasha Clinic Center. The results of this study indicate that the Applied form of Interpersonal Communication: Front office staff’s interpersonal communication in handling patient complaints tends to include active listening practices, verbal and non-verbal empathy, clarity in the delivery of information and solutions, as well as responsiveness in promptness and promptness. These forms of communication are crucial in building positive interactions and demonstrating concern for patients. Additionally Supportive and Barrier Factors: The effectiveness of interpersonal communication is supported by the presence of adequate communication training, clear Standard Operating Procedures (SOPs) for handling complaints, a supportive work environment, and mastery of service information by staff. However, there were barriers such as high workload during peak hours, intense emotional conditions of patients, limited authority of staff in complaint decision-making, and lack of instant feedback mechanisms from patients.